2004
DOI: 10.1002/ijc.20441
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB alleles are differentially expressed by tumor cells in breast carcinoma

Abstract: The biologic and prognostic significance of HLA-DR expression and T-cell infiltration in breast carcinoma are presently controversial. To test the hypothesis that these factors are influenced by particular HLA-DRB alleles, 52 breast tumor samples, composed of 26 DRB1*04 and 26 non-DRB1*04 tumors, were assessed using immunohistochemistry for expression of DR and its associated invariant chain (Ii) and for infiltrating CD3 ؉ T cells. While DR expression by tumor cells was significantly associated with T-cell inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…To date, IHC staining of over 1000 surgically removed breast carcinoma lesions has shown that HLA class II antigens are often up-regulated on malignant tumors of mammary epithelial cells [14,19,23,24,26,32,[112][113][114][115][116][117][118][119][120][121]. As observed in colon and cervical epithelial cells [122,123], HLA class II antigen expression does not appear to be restricted to cells which have undergone malignant transformation, since IHC analysis has also identified HLA class II antigen expression in benign mammary lesions [19,23,26,114,115].…”
Section: Hla Class H Antigensmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, IHC staining of over 1000 surgically removed breast carcinoma lesions has shown that HLA class II antigens are often up-regulated on malignant tumors of mammary epithelial cells [14,19,23,24,26,32,[112][113][114][115][116][117][118][119][120][121]. As observed in colon and cervical epithelial cells [122,123], HLA class II antigen expression does not appear to be restricted to cells which have undergone malignant transformation, since IHC analysis has also identified HLA class II antigen expression in benign mammary lesions [19,23,26,114,115].…”
Section: Hla Class H Antigensmentioning
confidence: 99%
“…All the studies performed have investigated HLA-DR antigen expression [14,19,23,24,26,32,[112][113][114][115][116][117][118][119][120][121]124,125], while only five have examined HLA-DP and HLA-DQ antigen expression. In all five studies, irrespective of the frequency of HLA class II antigen detection in the breast carcinoma lesions analyzed, HLA-DR antigens have been found to be more frequently expressed than HLA-DQ and DP antigens [23,32,116,124,125].…”
Section: Hla Class H Antigensmentioning
confidence: 99%
See 3 more Smart Citations